Retinal Detachment Surgery and Proliferative Vitreoretinopathy From Scleral Buckling to Small Gauge Vitrectomy - Spandau, Ulrich; Tomic, Zoran; Ruiz-Casas, Diego; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This clinically oriented book provides a complete overview of retinal detachment and Proliferative vitreoretinopathy (PVR), a difficult surgical challenge faced by ophthalmologists. Small gauge vitrectomy offers new possibilities to tackle this difficult pathology however this surgical approach may differ from one retinal surgeon to the next. To reflect the various approaches to treating PVR, the book is divided up in three parts. In the first part the authors describe the complete variety of surgical techniques applied to retinal detachment. In the second section, the surgical approach for PVR detachment is demonstrated step-by-step. In the third part, a large variety of retinal surgeons from Europe discuss video case reports of PVR retinal detachment to give a complete overview of dealing with this complex retinal disorder. The book is practical, down to earth, the surgeries are explained in detail, illustrated with drawings, photographs and refers to a huge number of videos available via Dr. Spandau$1 (Bs YouTube channel.s
Proliferative Vitreoretinopathy (PVR): An Introduction -- Before Surgery -- Surgery -- After Surgery. Proliferative Vitreoretinopathy (PVR) An International Approach -- Surgical Trends and Case Reports. .
Keywords: Ophthalmology; Ophthalmology; Retinal Detachment -- surgery; Vitreoretinopathy, Proliferative -- surgery; Vitrectomy -- methods; Microsurgery -- methods